Advanced topics in LabWindows/CVI - Khalid, Shahid F., 1944- (National Instruments virtual instrumentation series., 2002)
Take virtual instrumentation to the next level with high-level programming. High-level programming with LabWindows/CVI Live data display via Internet or intranet sources Programmatic creation and control of GUIs Data acquisition and VXI device communication Graph control, table control, function panels, instrument drivers, and Open GL Unleash the true power of LabWindows/CVI when you employ the rich features of this programming environment. In this follow-up to his LabWindows CVI Programming for Beginners, Shahid F. Khalid presents the sophisticated techniques that allow experienced users to make the most of this virtual instrumentation powerhouse. The flexibility of LabWindows/CVI software means that you can build virtual instrumentation using Microsoft Visual Basic and Visual C++ as well as ANSI C. Advanced Topics in LabWindows/CVI focuses on the use of C in an open software architecture. It is a project-oriented guide that will teach you to build applications using the more complex features of this programming environment. Applications include: Live data acquisition via Internet or intranet sources using Data Socket technology GUI controls created and manipulated in real time Advanced features of graph and table controls 3-D data plotting with Open GL Communications with VXI devices using VISA Creating and using function panels and instrument drivers The material is organized to present information with maximum clarity, keeping the reader in mind. For convenience, each chapter concludes with an explanation of the purpose and prototype of the library functions under discussion. Advanced Topics in LabWindows/CVI will give students and working professionals the tools to build and automate sophisticated virtual instrumentation for a world of applications.